Identifying ecotourists' accommodation needs and preferences? - M. Saayman; P. van der Merwe (South African Journal of Business Management, 2017)
The purpose of this research is to determine ecotourists' needs and preferences concerning national parks in South Africa. A survey was conducted at the Tsitsikamma National Park, focusing on fixed-roof accommodation, camping and ecolodges. Results showed that the preferences for each aspect are unique and that setting remains paramount when it comes to fixed-roof accommodation. The research also confirmed that a variety of accommodation types, including provision for self-catering, is preferred by ecotourists. This research makes a valuable contribution to the managing of accommodation in South African National Parks.
Keywords: 650